Position and orientation analysis of Jupiter robot arm for navigation stability - Shalash, Omar; Sakr, Adham; Salem, Yasser; Abdelhadi, Ahmed; Elsayed, HossamEldin; El-Shaer, Ahmed (Institute of Advanced Engineering and Science, 2025)
Jupiter robot has made a great impact in the educational field with its support for autonomous navigation, visual perception, and many other features from its artificial intelligence platform's learning box. This study undertakes a kinematic model design of Jupiter's arm to aid the robot's motion stability. This process involved the determination of a homogeneous transformation matrix, followed by the determination of orientation, position, and Euler angles. Ultimately, the homogeneous transformation matrix was successfully derived, and the simplification of direct kinematic matrices was achieved. Consequently, the kinematic analysis for Jupiter's arm was established using the position Denavit–Hartenberg method, orientation, and Euler angles, proving to be valuable in the context of this research.